2018
DOI: 10.1590/0103-6440201801760
|View full text |Cite
|
Sign up to set email alerts
|

Apically extruded debris in filling removal of curved canals using 3 NiTi systems and hand files

Abstract: The aim of this study was to assess the amount of apically extruded debris during filling removal with WaveOne Gold (WOG), ProTaper Universal Retreatment (PTR), D-RaCe Retreatment (DRR) or hand files (HF), to compare the working time during filling removal, and to describe failures of NiTi instruments. Forty mesiobuccal roots of maxillary first molars were prepared with WOG Primary, obturated and divided into 4 groups (n=10), according to the instruments used: WOG, PTR, DRR or HF. Distilled water was used as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 35 publications
1
47
0
3
Order By: Relevance
“…The quantification of extruded debris was done in the laboratory by using an experimental model well-defined to collect the debris, in addition to an analytic balance of high sensitivity used. Contrary to most of the published studies where evaluation of apical extrusion was performed with a WL of 1 mm from the apical foramen, 10,11,30,31 the instrumentation of the canal system was accomplished at the foramen and beyond, which might limit comparison with previous studies. Most studies related to this subject have calculated the amount of extrusion of debris after instrumentation at the WL which corresponds to the apical constriction.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The quantification of extruded debris was done in the laboratory by using an experimental model well-defined to collect the debris, in addition to an analytic balance of high sensitivity used. Contrary to most of the published studies where evaluation of apical extrusion was performed with a WL of 1 mm from the apical foramen, 10,11,30,31 the instrumentation of the canal system was accomplished at the foramen and beyond, which might limit comparison with previous studies. Most studies related to this subject have calculated the amount of extrusion of debris after instrumentation at the WL which corresponds to the apical constriction.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies related to this subject have calculated the amount of extrusion of debris after instrumentation at the WL which corresponds to the apical constriction. 10 To the investigators' knowledge, no study has reported extrusion of debris beyond the foramen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies presented that some mechanical nickel-titanium (Ni-Ti) instruments, in particular rotary and reciprocating systems, exhibited e ciency in root canal retreatment [11,12,13,14,15,16,17]. In these studies, Protaper Universal Retreatment (PTR) system, Waveone Gold (WOG) system, and Reciproc Blue (RB) system are regularly applied to curved root canal retreatment.…”
Section: Introductionmentioning
confidence: 99%